The Cobble Street Cousins : a little shopping - Rylant, Cynthia; Halperin, Wendy Anderson (New York : Aladdin Paperbacks, 2000)
Rosie, Lily, and Tess, three cousins who are living together with their aunt, decide to make a miniature flower shop just like Aunt Lucy's real shop, and give it to her as a gift.
Book Links (A.L.A.)
Booklist
Bulletin (Center for Children's books)
7.2
5-8
5-8
Keywords: Aunts -- Fiction; Cousins -- Fiction; Cousins -- Fiction